Analysis and Design of Mobile Revival TV Shop Application Information Systems - angellia debora suryawan (Ultima InfoSys : Jurnal Ilmu Sistem Informasi, 2023)
Mobile phone technology has undergone developments which makes it can provide a variety of facilities to support productivity and efficiency in the form of smartphones. Emarketer digital marketing research institute estimates that in 2018 there will be more than 100 million active smartphone users in Indonesia. In early 2019, the number of smartphone users reached 355 million, which more than 33% of the total population of Indonesia reached 268.2 million. With the large number of smartphone users, the number of mobile application downloads will also increase. This phenomenon is accompanied by the development of Esports (Electronic Sports) in Indonesia. The method used for the design and manufacture of systems in this thesis is the SDLC (System Development Life Cycle) method, because the data that the authors obtained from RevivalTV are suitable with this methodology.